2014
DOI: 10.17675/2305-6894-2014-3-1-035-047
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sulfate dihydrate (gypsum) scale inhibition by PAA, PAPEMP, and PAA/PAPEMP blend

Abstract: The effects of poly(acrylic acid), PAA, polyamino polyether methylene phosphonic acid, PAPEMP, and PAA/PAPEMP blend on calcium sulfate dihydrate (gypsum) are reported in this paper. It has been found that gypsum inhibition by PAA increases with increasing PAA concentration. Among the various phoshonates (i.e., aminotris(methylene phosphonic acid), AMP; hydroxyphosphono acetic acid, HPA; hydroxyethylidene 1,1-diphosphonic acid, HEDP; 2-phosphonobutane 1,2,4-tricarboxylic acid, PBTC; and polyether polyamino phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…These results clearly show that polymer containing non-ionic charge functional group is an ineffective gypsum growth inhibitor. It should be noted that the results obtained in the present investigation are consistent with previous published work on the performance of homopolymers of acrylamide and 2-ethyloxazoline (containing non-ionic (neutral charge) functional groups) [13,20]. It is worth noting that whereas homopolymer of 2-ethyloxazline exhibits poor performance as gypsum inhibitor, this polymer has been reported to show excellent performance for silica polymerization [21].…”
Section: Homopolymerssupporting
confidence: 91%
“…These results clearly show that polymer containing non-ionic charge functional group is an ineffective gypsum growth inhibitor. It should be noted that the results obtained in the present investigation are consistent with previous published work on the performance of homopolymers of acrylamide and 2-ethyloxazoline (containing non-ionic (neutral charge) functional groups) [13,20]. It is worth noting that whereas homopolymer of 2-ethyloxazline exhibits poor performance as gypsum inhibitor, this polymer has been reported to show excellent performance for silica polymerization [21].…”
Section: Homopolymerssupporting
confidence: 91%
“…twofold increase in %D value. It is worth noting that a trend in PA concentration vs. %D profiles similar to that observed in the present study has been reported for iron oxide and clay [3,5].…”
Section: Performance Of Synthetic Polymerssupporting
confidence: 89%
“…The effectiveness of polymers as dispersants for clay, calcium phosphate, silica, magnesium silicate, and iron oxide has been investigated by several researchers. Results of these studies reveal that polymers containing different functional groups i.e., carboxyl, sulfonic, amide, ester, etc., exhibit good to excellent dispersancy activity [3,4,5]. Dubin [6] in his study on the evaluation of polyphosphates, phosphonates, and homopolymers of acrylic acid, maleic acid, and acrylic/maleic acid-based copolymers as dispersants for iron oxide showed that copolymers performed better than polyphosphates and phosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…A widely used technique for controlling scale deposition is an application of chemical inhibitors [2,[5][6][7][8]. Commonly used commercial antiscalants are represented mostly by three chemical families: polyphosphates, organophosphonates and organic polyelectrolytes (polyacrylates (PA), and polycarboxysulfonates (PCS)).…”
Section: Introductionmentioning
confidence: 99%